Effect of different nitrogen levels and irrigation techniques on the ruminal degradation of the crude protein of maize - Barajas, R.; Díaz, T.; Flores, L. R.; Partida, L.; Martínez, Mayuly; Lomelí, J. J.; Velázquez, T de J. (Cuban Journal of Agricultural Science, 2016)
In order to determine the effect of ruminal degradation of maize crude protein obtained with two levels of nitrogen (300 and 400 kg ha-1) and two irrigation techniques (gravity and drip), dacron bags (10 x 18 cm) which contained 5 g of maize were used. By introducing a cannula, the bags were inoculated for 0, 3, 6, 12 and 24 h in the rumen of four heifers. A completely randomized design was applied with factorial arrangement 2x2 of the treatments (nitrogen and irrigation technique).There were not statistical differences between the interactions of the variables under study (P < 0.05).However, drip irrigation vs gravity (8.72 vs 8.05%) and fertilization with 400 vs 300 kg de N ha-1 (8.52 vs. 8.25 %) increased (P ≤ 0.05) the crude protein content of the grain. The treatments did not affect (P ≥ 0.21) the PC solubility (19.4 ± 2.85 %).The ruminal degradation of the maize CP in the different incubation times did not change (P ≥ 0.20) by the maize grain obtained by means of irrigation technique or N levels used in maize production. The ruminal degradation rate of CP (0.10 ± 0.03) did not change (P ≥ 0.13) by the treatments. The percentage of crude protein effectively degraded in the rumen (42.14 ± 2.83 %) was similar (P ≥ 0.48) between treatments. Although the schemes of nitrogen levels or irrigation technique can modify the crude protein content in the maize grain, this did not influence on the characteristics of ruminal degradation of its crude protein. Key words: irrigation techniques, fermentation pattern, solubility.